2021
DOI: 10.3390/s21082593
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Risk Assessment According to the Revised NIOSH Lifting Equation: A Preliminary Study Using a Wearable Inertial Sensor and Machine Learning

Abstract: Many activities may elicit a biomechanical overload. Among these, lifting loads can cause work-related musculoskeletal disorders. Aspiring to improve risk prevention, the National Institute for Occupational Safety and Health (NIOSH) established a methodology for assessing lifting actions by means of a quantitative method based on intensity, duration, frequency and other geometrical characteristics of lifting. In this paper, we explored the machine learning (ML) feasibility to classify biomechanical risk accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Several tools can be used to perform ML analyses: Tougui et al performed a study on these tools in the context of heart disease classification [41] and identified Knime analytics platform as the best tool in terms of data manipulation, creating complex workflows, parameter tuning, and control of the algorithms. Moreover, this tool has already been used to perform biomedical studies also in fields such as ophthalmology and signal processing [42][43][44], and in cardiology [45,46].…”
Section: Machine Learning: Tool and Algorithmsmentioning
confidence: 99%
“…Several tools can be used to perform ML analyses: Tougui et al performed a study on these tools in the context of heart disease classification [41] and identified Knime analytics platform as the best tool in terms of data manipulation, creating complex workflows, parameter tuning, and control of the algorithms. Moreover, this tool has already been used to perform biomedical studies also in fields such as ophthalmology and signal processing [42][43][44], and in cardiology [45,46].…”
Section: Machine Learning: Tool and Algorithmsmentioning
confidence: 99%
“…The proposed models may be able to be improved by utilizing body kinematic data. Such data were used to estimate biomechanical risk factors for lifting in two previous studies [35], [36]. The Varrecchia et al study classified the lifting index of the RNLE using kinematic features collected by a reflective marker-based motion capture system, while the Dopnisi et al study predicted one lifting index level using one IMU device on the lower back.…”
Section: Discussionmentioning
confidence: 99%
“…ML algorithms were implemented through the artificial intelligence platform Knime Analytics Platform (version 3.7.1), which is increasingly diffused in the scientific literature [ 38 , 39 , 40 ] and has achieved an interesting performance when compared with other platforms and programming languages.…”
Section: Methodsmentioning
confidence: 99%